2021
DOI: 10.3389/fonc.2021.707473
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors Stimulate HLA Class I Expression by Augmenting the IFNγ/STAT1 Signaling in Hepatocellular Carcinoma Cells

Abstract: Combination treatment with tyrosine kinase inhibitors (TKIs) and immunotherapies has shown efficacy in the treatment of multiple cancers, but the immunomodulatory effect of TKIs on the tumor cell phenotype remains unknown in hepatocellular carcinoma (HCC). Given that human lymphocyte antigen class I (HLA-I) is essential for tumor antigen presentation and subsequent antitumor immunity, we examined the effects of regorafenib, as well as other TKIs (sorafenib, lenvatinib and cabozantinib) on HLA-I expression in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Highly and differentially expressed mRNAs identified in this study suggested a new immunomodulatory activity of ICD inducers resulting in the regulation of antigen presentation, a crucial step for proper activation of the immune system antitumor response. Indeed, enrichment analysis demonstrated that the MHC-I pathway was upregulated, as previously reported [ 45 , 46 ], whereas MHC-II was downregulated. An in silico analysis of publicly available database [ 16 ] showed high concordance with our results, generalizing our findings, especially those regarding the downregulation of class II MHC molecules, an event associated to ICD induction altogether rather than to the specific ICD-inducing anticancer treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Highly and differentially expressed mRNAs identified in this study suggested a new immunomodulatory activity of ICD inducers resulting in the regulation of antigen presentation, a crucial step for proper activation of the immune system antitumor response. Indeed, enrichment analysis demonstrated that the MHC-I pathway was upregulated, as previously reported [ 45 , 46 ], whereas MHC-II was downregulated. An in silico analysis of publicly available database [ 16 ] showed high concordance with our results, generalizing our findings, especially those regarding the downregulation of class II MHC molecules, an event associated to ICD induction altogether rather than to the specific ICD-inducing anticancer treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Importantly, MKIs were shown to induce immunomodulatory effects. For instance, previous studies demonstrated that exposure to MKIs including sorafenib and regorafenib can stimulate MHCI synthesis and expression of other components of the antigen presentation pathway in cancer cells and, consequently, stimulate their elimination by cytotoxic lymphocytes ( Kwilas et al, 2014 ; Tsai et al, 2017 ; Takahashi et al, 2021 ). At the same time, little is known regarding the effect of MKIs on specifically the expression of non-constitutive proteasomes in cancer in general and in colorectal cancer in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, considerably higher expression of immuno-proteasome subunits was shown in melanoma tissue infiltrated with CD3 + T-cells ( Woods et al, 2016 ). IFN-γ-induced stimulation of MHC I and immunoproteasome subunit expression was in turn augmented by MKIs in hepatocellular carcinoma cells ( Takahashi et al, 2021 ). Thus, treatment with such inhibitors affect generation and presentation of cancer antigens acting in a synergic manner with endogenous immune molecules and by this mean stimulate recognition of cancer cells by the immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, ZIKV restores the expression of HLA-A in HLA-A KD U251 cells by 48 hpi; therefore, further experiments need to be conducted to better understand ZIKV infection. Moreover, the use of potential pharmaceutical compounds like MG132, a PSMA2 inhibitor known to exert anti-viral activity against HSV-1, trematinib which increases HLA-A expression via IFN gamma/STAT1 signaling and STAT3 activation and other tyrosine kinase inhibitors, need to be employed to identify novel anti-viral compounds against ZIKV infection [ 118 , 119 , 120 , 121 ]. The similarities and novelties of the current study in comparison to previously published omics studies help us understand some of the findings from this study better and further experiments need to be conducted to explain some of these differences and similarities across different cell types and omics platforms.…”
Section: Discussionmentioning
confidence: 99%